Fatal pancreatic fistula after laparoscopic distal pancreatectomy for intraductal papillary mucinous carcinoma with pancreaticobiliary maljunction and sphincterotomized papilla: a case report - Yoshifumi Morita; Tomohiro Akutsu; Mitsumasa Makino; Miku Obayashi; Shinya Ida; Ryuta Muraki; Ryo Kitajima; Amane Hirotsu; Makoto Takeda; Hirotoshi Kikuchi; Yoshihiro Hirmatsu; Yasushi Hamaya; et al. (Surgical Case Reports)
Abstract Background Pancreatic juice is constantly activated by contaminated bile in patients with pancreaticobiliary maljunction (PBM). Here, we report a case of laparoscopic distal pancreatectomy for a patient with PBM and sphincterotomized papilla, resulting in fatal pancreatic fistula. Case presentation A 79-year-old man was diagnosed with pancreatic intraductal papillary mucinous neoplasm and common bile duct stones. Endoscopic sphincterotomy was performed prior to surgery. The pancreatic duct was simultaneously visualized when the contrast agent was injected into the common bile duct. Sudden bleeding was observed from the abdominal drain on postoperative day (POD) 6. Emergent stent graft placement and coil embolization were performed for bleeding from the splenic artery. On POD 9, the drainage fluid changed to yellowish in color with bile contamination. For internal drainage of the digestive fluid, endoscopic retrograde biliary tube and pancreatic drainage tube were placed. On POD 24, second emergent coil embolization was performed for bleeding from the left gastric artery. On POD 25, open abdominal drainage was performed. On POD 32, third emergent coil embolization was performed for bleeding from the gastroduodenal artery. Subsequently, remnant pancreatic resection was performed. On POD 39, massive bleeding was again observed from the abdominal drain. Emergency arterial portography revealed bleeding in the right wall of the superior mesenteric vein. The patient died of hemorrhagic shock on the same day. Conclusions The extreme risk of severe pancreatic fistula after distal pancreatectomy should be considered in patients with PBM and sphincterotomized papilla. In this extraordinary situation, surgeons should promptly decide whether to resect the remnant pancreas to prevent losing the patient.